Remoção de células de cianobactérias por processos de sedimentação e flotação por ar dissolvido: avaliação em escala de bancada - Lucas Milani Santiago (2008)
The increase of nutrients in water supply reservoirs may affect water quality and its usage. One of the possible problems is the blooming of cyanobacteria. Cyanobacterial cells occurrence in raw water may increase treatment difficulty and hence its cost, but the main sanitary concern involves the release of cyanotoxins which might cause fatal damages to human health. This work evaluated the efficiency of dissolved air flotation (DAF) and sedimentation processes in treating raw waters with a cyanobacterial biomass of 105 cells/mL of cocoid M. protocystis cells and C. raciborskii filamentous, using laboratory apparatuses of bench-scale jartest and flotest, with distilled water spiked with cyanobacterial cells. Two coagullants have been used: aluminum sulphate and ferric chloride, for two superficial application taxes. The qualitative analyses of the coagulation diagrams showed that both sedimentation and DAF experiments with C. raciborskii resulted in lower efficiency in turbidity removal values compared to M. protocystis experiments. Experiments with ferric chloride resulted in low reprodutibility with the variation of coagulation pH, but its performance was better than alum in the sedimentation experiments. In some results of both experiments, ferric chloride brought a deterioration of studied water quality. Alum performed better than ferric chloride in overall DAF experiments, with visible greater efficiency in the removal of cocoid cells. In the experiments in which comparison was possible, DAF performed better than sedimentation, for lower coagulant dosages and lower coagulation pH. A statistical analyses has been conducted for pairs of selected experiments where matching was possible. DAF performed better statistically with cocoid cells than filamentous cells, using alum, and surpassed sedimentation results for C. raciborskii. There werent relevant statistical differences between sedimentation and DAF when using ferric chloride with filamentous. It has been proved that DAF obtains better results in the removal of cells than filamentous when alum is used.